Bulk RNA Sequencing With Integrated Single-Cell RNA Sequencing Identifies BCL2A1 as a Potential Diagnostic and Prognostic Biomarker for Sepsis - Li, Jun; Zhou, Mi; Feng, Jia-Qi; Hong, Soon-Min; Yang, Shao-Ying; Zhi, Lang-Xian; Lin, Wan-Yi; Zhu, Cheng; Yu, Yue-Tian; Lu, Liang-Jing (Frontiers in Public Health, 2022)
Background：Sepsis is one of the leading causes of morbidity and mortality worldwide in the intensive care unit (ICU). The prognosis of sepsis strongly depends on rapid diagnosis and appropriate treatment. New sepsis-related biomarkers are needed urgently and their efficiency should be carefully demonstrated. Methods: Differential expression analysis and weighted gene co-expression network analysis (WGCNA) were applied to detect sepsis and monocyte/macrophage-related genes. Least absolute shrinkage and selection operator (LASSO) and random forest regression analyses were used in combination to screen out prognostic genes. Single-cell RNA sequence profiling was utilized to further verify the expression of these genes on a single cell level. Receiver operating characteristic (ROC) curve and decision curve analysis (DCA) were also appiled to verify the diagnostic value of the target biomarkers. Results: The intersections of the genes detected by differential expression and WGCNA analyses identified 141 overlapping candidate genes that were closely related to sepsis and macrophages. The LASSO Cox and random forest regression analyses further screened out 17 prognostic genes. Single-cell RNA sequencing analysis detected FCGR1A and BCL2A1 as potential biomarkers for sepsis. The diagnostic efficacy of BCL2A1 was further validated using ROC curve analysis and DCA. Conclusion: It was revealed that BCL2A1 had good diagnostic and prognostic value for sepsis, and that it can be applied as a potential and novel biomarker for the management of the disease.